Delayed nivolumab‐induced hepatotoxicity during pazopanib treatment for metastatic renal cell carcinoma: An autopsy case. Issue 5 (3rd August 2019) - Todo, Maki; Kondo, Hideyuki; Hayashi, Taiki; Masuda, Tsukasa; Okabe, Takashi; Kaneko, Go; Oyama, Masafumi; Shirotake, Suguru; Nishimoto, Koshiro
Abstract : Introduction: Pazopanib, a tyrosine kinase inhibitor, and nivolumab, an immune checkpoint inhibitor, are both considered to cause hepatotoxicity with different pathophysiology. We report a case in which a patient died of severe hepatotoxicity who was presumed to have been caused by the administration of nivolumab followed by pazopanib for metastatic renal cell carcinoma. Case presentation: A 74‐year‐old male with metastatic renal cell carcinoma was treated with nivolumab as a third‐line treatment. However, nivolumab was subsequently discontinued, as it caused severe thyroiditis. About 2 months after the final dose of nivolumab was administered, pazopanib was initiated as a fourth‐line treatment. The patient suffered from lethal hepatic failure and died 18 days after the initiation of pazopanib treatment. An autopsy revealed that CD8‐positive lymphocytes had infiltrated the thyroid gland and liver. Conclusion: The patient was considered to have died of severe hepatic failure due to the aggravation of mild nivolumab‐induced immune‐related hepatitis by pazopanib.